Translation status – a professional approach - Barabé, Donald (The Journal of Specialised Translation, 2021)
Translation plays a crucial role in today's globalised and interconnected world. Yet, it seems that no one can prevent an unqualified person from translating (Pym et al. 2012). This situation raises a number of fundamental questions: is it a problem that anyone can translate and, if so, to whom and how?; is translation a formal profession and, if not, should it become one?; if it is a formal profession or if it becomes one, should it be regulated and, if so, why and how? Before answering these questions, mostly by the affirmative, this article examines the current status of translation as a profession as well as the main causes and effects of this status. It shows that the concept of risk of prejudice due to incompetent translation should be at the heart of the positioning of translation as a profession. It also shows that prejudicial texts (see definition) must imperatively be translated by qualified translators and that social interest, namely ensuring public protection against erroneous translations, should take precedence over professional interest, i.e., the promotion of translators, for the full recognition of the translation profession.